Exploration of Isosteric Replacement of Imidazolidinone Motif in 4-Phenyl-1-arylsulfonylimidazolidinone with Pyrazole and Pyrazolidinone for Cytotoxicity - Subramanian, Santhosh; Sharma, Vinay K.; Yun, Jieun; Jung, Sang-Hun (Bulletin of the Korean Chemical Society, 2014)
To investigate the possible isosteric replacement of imidazolidinone moiety in 4-phenyl-1-arylsulfonylimidazolidinones (2) for broad and potent anti-cancer agents, a series of 5-phenyl-1H-pyrazol-3-yl 1- (acyl)indoline-5-sulfonates (4) and 1-(1-(acyl)indolin-5-ylsulfonyl)-5-phenylpyrazolidin-3-ones (5) were prepared and evaluated for their cytotoxicity against six human cancer cell lines. Although the pyrazoles 4 or pyrazolidinones 5 showed relatively good activity, still they showed lesser activity in comparison to imidazolidinones 2. These activity decreases could be interpreted with the effect of change of the hydrogen bonding characteristics and the substitution pattern on structural variations of five membered rings from imidazolidinones 2 to pyrazoles 4 and pyrazolidinones 5, respectively. Therefore, it can be concluded that 4- phenyl-1-arylsulfonylimidazolidinone is a basic pharmacophore of imidazolidinones 2. KCI Citation Count: 3